Flouting of Maxim as a Representation of Indonesian Social Issues in Si Nopal Animated Series - Arvi, Reva Febrika; Zaim, M. (Universitas Negeri Padang, 2024)
Speakers are supposed to follow cooperative principles during the communication process in order to deliver messages effectively. Nevertheless, many speakers disregard it for some reasons. Flouting of maxim is one of the situations in which speakers fail to observe the maxim in order to generate an implicature. This research aimed to analyze the types and the strategies of flouting of maxim and its representations to Indonesian social issues in Si Nopal animated series. This research used descriptive method. The data of this research were the utterances of the characters in Si Nopal animated series. It is found that there were total of 50 utterances that flout the maxim. The result shows that the type of maxim of quantity with providing too much information strategy was the most common type of flouting of maxim found in the data. Moreover, this research also found that there are some Indonesian social issues represented through flouting of maxim in Si Nopal animated series, which mockery and capitalism are two issues that occurred more frequent in comparison to other issues. This research implicated that the characters in Si Nopal animated series flout the maxim and represent issues by flouting maxim in order to respond utterances.